The Survival Rate, Growth, and Health of Scalloped Spiny Lobster, Panulirus Homarus (Linnaeus 1758) in Nursery and Grow-Out in A Concrete Tank Fed with Fresh Food and Three Kinds of Dry Pellet - Slamet, Bejo; Sudewi; Rusdi, Ibnu; Haryanti; Astuti, N. Widya; Fahrudin; Giri, N. Adiasmara (Migration Letters, 2023)
This study aimed to determine the best feed for Panulirus homarus nursery and grow-out in a concrete tank. The treatments were fresh food (A) pellets for grouper (B), pellets for shrimp (C), and pellet formula (D). The study of the nursery with an initial total length (TL) of 2.2±0.043 cm and body weight (BW) of 0.32±0.023 g, while the grow-out with an initial TL of 13.1±0.18 cm, BW of 78±2.7g. Feeding 2x/day for fresh food in the nursery was 20% biomass/day and 10% biomass/day at grow-out. For dry pellet feed in the nursery, 5% biomass/day, while in grow-out, 2% biomass/day. The observed parameters are survival rate (SR), TL, BW, THC, and the BRIX index. The results show that SR on the nursery (P<0.05) was highest in D (55.1%), followed by B (49.5%), C (37.3%), and A (23.2%), while on the grow-out (p<0.05) highest on D (94.67%), followed by B (84.25%), C (82.67%), and A (50.67%). The final biomass in the nursery (p<0.05) was highest on D (436.39), followed by B (351.95 g), C (230.89 g), and A (178.64 g), while on the grow-out (p<0.05), highest on D (9.659 kg), followed by B (7.056 kg), C (7.056 kg), and A (4.826 kg). The Best lobster health is on the D, followed by B, C, and A. From this result, the best feed is the pellet lobster formula, followed by the pellet for grouper, the pellet for shrimp, and fresh food.